Transport of congestion in two-phase compressible/incompressible flows. (August 2018) - Degond, Pierre; Minakowski, Piotr; Zatorska, Ewelina
Abstract: We study the existence of weak solutions to the two-phase fluid model with congestion constraint. The model encompasses the flow in the uncongested regime (compressible) and the congested one (incompressible) with the free boundary separating the two phases. The congested regime appears when the density in the uncongested regime ϱ ( t, x ) achieves a threshold value ϱ ∗ ( t, x ) that describes the comfort zone of individuals. This quantity is prescribed initially and transported along with the flow. We prove that this system can be approximated by the fully compressible Navier–Stokes system with a singular pressure, supplemented with transport equation for the congestion density. We also present the application of this approximation for the purposes of numerical simulations in the one-dimensional domain.